Noninvasive Longitudinal Study of a Magnetic Resonance Imaging Biomarker for the Quantification of Colon Inflammation in a Mouse Model of Colitis. Issue 6 (June 2016) - Bianchi, Andrea; Bluhmki, Teresa; Schönberger, Tanja; Kaaru, Eric; Beltzer, Anne; Raymond, Ernest; Wunder, Andreas; Thakker, Paresh; Stierstorfer, Birgit; Stiller, Detlef
Abstract : Background: Colonoscopy is the gold standard to diagnose and follow up the evolution of inflammatory bowel diseases. However, this technique can still present a risk of severe complications, a general discomfort in patients, and its diagnostic value is limited to the visualization of the colon mucosal changes. Magnetic resonance imaging (MRI) is emerging as a noninvasive imaging technique of choice to overcome these limitations. The aim of this work was to evaluate the potential of colon wall thickness measured using MRI as an in vivo imaging biomarker of inflammation for inflammatory bowel disease in an animal model of this disease. Methods: On day 0, 2% or 3% Dextran sodium sulfate was added to the drinking water of mice (n = 10/group) for 5 days. Six mice were left as controls. Animals were imaged with colonoscopy and MRI on days 7, 11, and 21 to study the colitis progression. Histology was performed at the end of the protocol. Results: The colon wall thickness measured in Dextran sodium sulfate–treated animals was shown to be significantly and dose dependently increased compared to controls. Colonoscopy showed similar results and excellently correlated with MRI measurements and histology. The proposed protocol showed high robustness, with negligible interoperator and intraoperator variability. Conclusions: The findings of this investigation suggest the feasibility of using MRI for the noninvasive assessment of colon wall thickness as a robust surrogate biomarker for colon inflammation detection and follow-up. The data presented show the potential of MRI in in vivo preclinical longitudinal studies, including testing of new drugs or investigation of inflammatory bowel disease development mechanisms. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 22 April 2016.